The Discourse of Development Progress and Poverty Alleviation in Dumai City - Rizky Setiawan; M. Irfan Rosadi; Safira Alya Zulaikha; Jihan Indriyani (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Discourse is an indispensable topic in social theory, with work spanning fields such as sociology, anthropology, continental philosophy, and discourse analysis. This study aims to describe explicitly and comprehensively the discourse of poverty and development. This objective is achieved by presenting the background of the empirical conditions of the focus of the research study through the existing discourse ideas by looking at the phenomena of Development and Poverty in Dumai City. This research focuses on the development of infrastructure development and poverty alleviation. Development development often ignores poverty alleviation. Data obtained from the Dumai City Central Statistics Agency in 2023 showed 10.15 thousand people, an increase from the previous year in 2022 of 10 thousand people. Seeing this phenomenon, the author is interested in examining the symptoms that emerge to find a coherent model between development progress and poverty alleviation. The method and type in this study are Qualitative Descriptive. The informant drawing technique uses the Proposive Sampling technique and the data collection technique in this study is interviews, observations, literature studies and documentation. Keywords: Discourse, Development and Poverty.